2016
DOI: 10.1007/s40534-016-0108-4
|View full text |Cite
|
Sign up to set email alerts
|

A technical review on persistent scatterer interferometry

Abstract: This article focuses on reviewing the technologies of persistent scatterer interferometry (PSI), which has been often used to monitor the deformation of Earth surface. Three critical steps in the implementation of PSI were introduced, i.e., (1) detection of persistent scatterer (PS), (2) construction of PS network, and (3) PSI modeling and solution. Finally, the main problems and outlooks on the PSI technique are discussed and given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Many diverse mixed methods and solutions exist within each group. A broad overview of these methods can be found in [1,17,29,30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many diverse mixed methods and solutions exist within each group. A broad overview of these methods can be found in [1,17,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of the ambiguous nature of the observation (the wrapped interferometric phases), one of the main disadvantages of TS-InSAR methods is their inability to detect "fast" deformations. If the differential deformation phase between two subsequent acquisitions exceeds an interval of −π to π, the real deformation rate cannot be entirely captured [29,30]. Ambiguity in the unwrapping procedure results in the limitation of the maximum differential deformation rate falling between two neighboring points.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Siddique et al [20], the authors demonstrated that the SAR tomography method can add the improved value in deformation sampling in areas affected by layover. In addition, by the virtue of SAR tomography, the scatterer's elevation and intensity are considered in the analysis, solving a question posed by Jia and Liu [41].…”
Section: The Related Psi Techniques and Advancementsmentioning
confidence: 99%
“…The PSI is a suitable technique to monitor dam deformation that allows to gather data on its subsidence [8,[12][13][14][15][16][17]. A detailed description of the DInSAR and PSI and their applications can be found in [7,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%